دراسة تأثير تبريد الألواح الكهروشمسية بالماء على مردودها وطاقتها الكهربائية المتولدة - حمودي, علي (Latakia University Journal -Engineering Sciences Series, 2014)
يتأثر الأداء الكهربائي للألواح الكهروشمسية بشكل كبير بدرجة حرارة تشغيل الخلايا الكهروشمسية السيليكونية بسبب خصائص السيليكون البلوري المستخدم فيها, فتنخفض الطاقة المتولدة من هذه الخلايا بارتفاع درجة حرارتها. وللحد من هذا الانخفاض في الطاقة تم تبريد الألواح الكهروشمسية باستخدام الماء, وذلك بوضع أنبوب يحوي ثقوب عديدة منتظمة على أعلى اللوح ويجري الماء بشكل حر على سطحه بعدة تدفقات. فعند التدفق (4.224 l/min.m2) , انخفضت درجة حرارة اللوح بمقدار حتى (20C°), والزيادة المسجلة في الناتج الكهربائي خلال يوم كامل حوالي (12.8%), وارتفع المردود من (8.31%) إلى (9.62%) أي بمقدار (1.31%). وعند التدفق (3.167 l/min.m2), انخفضت درجة حرارة اللوح بمقدار حتى (18C°) , والزيادة المسجلة في الناتج الكهربائي حوالي (9.8%) , وارتفع المردود بمقدار (1.03%). أما عند التدفق (2.112l/min.m2), انخفضت درجة حرارة اللوح بمقدار حتى (15.5C°), والزيادة المسجلة في الناتج الكهربائي حوالي (7.8%), وارتفع المردود بمقدار (0.83%). كما أن جريان الماء على سطح اللوح الكهروشمسي يقلل ضياعات الانعكاس, لأن قرينة انكسار الماء (1.3) متوسط بين قرينة انكسار الهواء (1) والزجاج (1.5), بالإضافة لذلك يبقى سطح اللوح نظيفاً. The electrical performance of the PV modules can be severely affected by operating temperature of silicon cells due to properties of the crystalline silicon used; the energy generated from these cells decreases with their high temperatures. To reduce this decline in energy, the PV modules use cooling water by placing a tube containing many regular holes on the top end of the module, and water flows on the surface freely in several flows. So, with flow rate (4.224 l/min.m2), module temperature decreases up to (20C°); the record of increased value of electrical yield over the whole day is about (12.8%). and efficiency rises (from 8.31% to 9.62%) of (1.31%). With Flow rate (3.167 l/min.m2), temperature of module decreases up to (18C°); the record of increased value of electrical yield is about (9.8%), and efficiency rises by (1.03%). But with flow rate (2.112 l/min.m2), temperature of module decreases up to (15.5C°); the record of increased value of electrical yield is about (7.8%), and efficiency rises by (0.83%). Furthermore, flow of water on the surface of PV module reduces the reflection losses because the refractive index of water with (1.3) is intermediate between air (1) and glass (1.5). In addition, the surface of module remains clean.